When Banks Grow Too Big for Their National Economies: Tail Risks, Risk Channels, and Government Guarantees. (22nd August 2018) - Hagendorff, Jens; Keasey, Kevin; Vallascas, Francesco
Abstract : Banks are growing ever larger compared to their national economies. We show that increases in relative bank size (measured as a bank's liabilities divided by national GDP) are linked to banks displaying higher tail risk. This effect is not entirely due to risk channels that disproportionately expose relatively large banks to systematic tail risks, sovereign risks, or banking crises. Instead, we detect a persistent component in the tail risk of relatively large banks that is bank-specific and connected to government guarantees. Furthermore, as banks grow in relative size, tail risks are shifted to debtholders without wealth gains for shareholders.